Alveolar Soft Part Sarcoma: Imaging Evaluation - Morimoto, Letícia dos Reis; Lederman, Henrique Manoel; Macedo, Carla Renata Donato; Amaral, Denise Tokechi; Barbosa, Lucas de Figueiredo; Guimarães, Júlio Brandão (Seminars in Musculoskeletal Radiology, 2025)
This case report concerns a 16-year-old boy who developed pain in his right thigh after a soccer game. Imaging studies revealed a pathologic transtrochanteric fracture of the right femur, accompanied by a large expansive intramuscular lesion centered in the deep planes of the adductor musculature. Main imaging findings included intense enhancement and vascularization of the lesion, along with peripheral and central flow voids, the latter described as characteristic of this subtype of soft tissue sarcoma. Alveolar soft part sarcoma is a rare and distinctive sarcoma with an indolent clinical course that typically occurs in young patients and predominantly affects the deep tissues of the lower limbs.
Keywords: alveolar soft part sarcoma; soft tissue sarcoma; magnetic resonance imaging